Exploring the do-it-yourself approach in subjective refraction - Raquel Salvador-Roger; José J. Esteve-Taboada; Sara Ferrer-Altabás; Vicente Micó; Alberto Domínguez-Vicent; Abinaya Priya Venkataraman (PLoS ONE, 2025)
Purpose To evaluate the precision and accuracy of a novel do-it-yourself (DIY) subjective refraction technique utilizing a manual tunable spherical lens and an adjustable astigmatic lens. Methods Sixty-six participants performed three self-refraction measurements using a DIY approach, while an optometrist conducted one measurement using the traditional subjective refraction methodology. The DIY approach relied on power vector analysis, where a tunable spherical lens and an adjustable astigmatic lens (Stokes lens), aligned to the participant’s eye, were rotated to obtain measurements. The study assessed refractive error, visual acuity, and required measurement time. Repeatability was evaluated using the coefficient of repeatability, and agreement between methods was analyzed using limits of agreement. Results The coefficients of repeatability for refractive error components (M, J0, J45) were ±0.38 D, ± 0.21 D, and ±0.21 D, respectively. Visual acuity showed a repeatability of ±0.06 logMAR, and the required time had a repeatability of ±55 seconds. The limits of agreement between the DIY approach and the traditional method were ±0.64 D, ± 0.36 D, and ±0.26 D for refractive error components, ± 0.04 logMAR for visual acuity, and ±127 seconds for required time. Conclusions The DIY approach can be considered a repeatable alternative among self-subjective refraction methods, although it is a first attempt and not yet fully automatic. While it cannot supplant traditional subjective refraction and further research would be required to address, it has the potential to be a viable option in certain specific cases, such as circumstances characterized by a lack of eye care professionals or humanitarian works.